Tax Avoidance in the Global Economy: Mechanisms, Impacts, and Regulatory Responses - Masruri, Mohamad Anwar; Rasiman, Rasiman; Asvariwangi, Verni; Fadilah, Rizal; Hurriyaturrohman, Hurriyaturrohman (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2025)
Tax avoidance remains a crucial issue in global fiscal policy, undermining the public revenue system and exacerbating economic inequality. This article synthesizes the latest research on tax avoidance mechanisms, socio-economic implications, and the ever-evolving regulatory framework. Using a systematic literature review, we analyzed peer-reviewed studies, policy documents, and empirical data from 2018 to 2024. Key findings reveal sophisticated strategies such as profit shifting, transfer pricing manipulation, and exploitation of tax havens, which are widely used by multinational corporations (MNEs) and high-income individuals (HNWIs). This article highlights the role of digitalization and crypto assets in facilitating non-transparent financial flows, while also evaluating the effectiveness of global initiatives such as the OECD's Base Erosion and Profit Shifting (BEPS) Project and the Global Minimum Tax Agreement. Policy recommendations focus on transparency, multilateral cooperation, and the use of adaptive technologies.